A Comparative Analysis of Partial Replacement of Yeast with CO2 Gas Hydrates as Leavening Agents in Baking of Wheat Bread - Srivastava, Shubhangi; Kollemparembil, Ann Mary; Zettel, Viktoria; Claßen, Timo; Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Delgado, Antonio; Jekle, Mario; Hitzmann, Bernd (Processes, 2023)
The aim of this study is to examine how CO2 gas hydrates (CO2 GH) are used in baking, notably in the creation of wheat bread, as a leavening agent. CO2 GH were produced with the use of food grade amino acids called promoters. The article emphasizes an interesting approach by using a hybrid combination of yeast and CO2 GH. The current study is based on a comparative evaluation of leavening agents in bread with (1) GH with promoters (20–70% GH) and (2) GH with promoters + yeast as a partial replacement (25–75%). The results obtained are then also compared with those of standard yeast bread along with the effects on wheat bread quality parameters such as volume, specific volume, hardness, moisture content, baking loss, and pore size. The GH bread with promoters had baking losses that were equivalent to the quality of traditional yeast bread. The breads with 60% and 70% GH with promoters had the best outcomes when compared with standard yeast bread. When a combination of CO2 GH with promoters (20–70%) and yeast (25–75%) was used in the study, the best combinations were obtained with 70% GH + 50% yeast and 70% GH + 75% yeast. Additionally, this article clarifies some potential future uses for CO2 GH as leavening agents in the bread industry, with a discussion of potential limitations as well as the cost efficiency of the developed technology. This information could help in the creation of new methods and standards for better CO2 GH selection for usage in other bakery goods.
CRIS-Team Scopus Importer:2023-04-14
Keywords: amino acids; bread; CO; leavening; promoters; yeast

A Comparative Analysis of Partial Replacement of Yeast with CO2 Gas Hydrates as Leavening Agents in Baking of Wheat Bread - Srivastava, Shubhangi; Kollemparembil, Ann Mary; Zettel, Viktoria; Claßen, Timo; Mohammad, Mohammad Mobarak; Gatternig, Bernhard; Delgado, Antonio; Jekle, Mario; Hitzmann, Bernd (Processes, 2023)

An Innovative Approach in the Baking of Bread with CO2 Gas Hydrates as Leavening Agents - Srivastava, Shubhangi; Kollemparembil, Ann Mary; Zettel, Viktoria; Claßen, Timo; Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Delgado, Antonio; Jekle, Mario; Hitzmann, Bernd (Foods, 2022)
Gas (guest) molecules are trapped in hydrogen-bonded water molecules to form gas hydrates (GH), non-stoichiometric solids that resemble ice. High pressure and low temperature are typical conditions for their development, with van der Waals forces joining the host and guest molecules. This article study investigates the application of CO2 gas hydrates (CO2 GH) as a leavening agent in baking, with particular reference to the production of wheat bread. The main intention of this study is to better understand the complex bread dough formed by CO2 GH and its impact on product quality. This may enable the adaptation of CO2 GH in baking applications, such as those that can specifically influence wheat bread properties, and so the final bread quality. The present research further examines the comparative evaluation of yeast bread with the GH bread’s impact on bread quality parameters. The amount of GH was varied from 10 to 60%/amount of flour for the GH breads. The GH breads were compared with the standard yeast bread for different quality parameters such as volume, texture, and pore analysis. The results show that the bread with 20% and 40% GH obtained the best results in terms of volume and pore size. Moreover, this article also sheds some light on the future applications of the use of CO2 GH as leavening agents in foods. This knowledge could help to create new procedures and criteria for improved GH selection for applications in bread making and other bakery or food products.
CRIS-Team Scopus Importer:2022-12-02
Keywords: bread; browning; CO; dough; food applications; leavening; leavening

CO2 gas hydrate as an innovative leavening agent for baked goods - Frühling, Yvonne; Claßen, Timo; Mobarak, Mohammad Mobarak; Bauer, Marius; Zettel, Viktoria; Gatternig, Bernhard; Hitzmann, Bernd; Delgado, Antonio (Future Foods, 2023)
In the presented research, the use and technical realization of CO2 gas hydrate (GH) as a novel baking agent is investigated. GH are ice-like structures where one mole of hydrate typically consists of about 85% water and 15% gas. Hydrates were formed in a lab-scale 1.1 L stirred tank reactor at 1-2 degrees C and 3.5 MPa, and transferred into a temperature-controlled, gas-tight measuring cell. The leavening effect of gas hydrates was assessed by measuring the CO2 release rates. Storage stability at-20 to 0 degrees C and stability above 0 degrees C were investigated experimentally and a coupled thermodynamic and kinetic decay model implemented. At-10 degrees C, gas release was highest in the first minutes and stopped completely after 5 days. After 21 days storage at-10 degrees C, the GH still contained 20 % of the initial gas content. Above 0 degrees C, dissociation rates were highly temperature dependent, and half value times ranged from 30 min (3 degrees C) to 4 min (20 -30 degrees C). Above 10 degrees C, ambient temperature had only a minor effect on the dissociation rates. Results from the kinetic decay model, applied for a 21 mm particle, showed similar dissociation behavior as a particle from experiments. Applying the model for a 3 mm particle, showed full dissociation after approximately 15 min. Stability and baking tests showed that CO2 hydrate is in principle suitable as a leavening agent. However, GH production still needs to be optimized and recipes for GH application require further development.
CRIS-Team WoS Importer:2023-04-14

Drying process simulation in food industry using lattice boltzmann method - Mobarak, Mohammad Mobarak; Hussein, Mohamed; Delgado, Antonio (3rd International Food Operations and Processing Simulation Workshop, FoodOPS 2017, 2017)
Keywords: Lattice Boltzmann Method; Drying Process; Phase Transition; Mass and Heat Transfer

Foam Drainage Parametric Study Using the Lattice Boltzmann Method Considering the Non-Newtonian Behavior - Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Delgado, Antonio; Bernstein, Thomas; Mchardy, Christopher; Rauh, Cornelia (Chemical Engineering & Technology, 2022)
Foam exists in several food and chemical processes. It often delays, contaminates, and obstructs the industrial process, which affects the product's quality and safety. Liquid drainage in foam is one of the most influencing physical phenomena impacting its behavior, and is characterized by its short time scales. The lattice Boltzmann method (LBM) is applied to develop a consistent method for evaluating the permeability of different foam structures, while considering the non-Newtonian behavior of its liquid lamella. Foam drainage for non-Newtonian fluids is not well understood and established in literature. Different geometrical and liquid parameters are thus considered and analyzed, in order to generate a map for the foam permeability.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Foam drainage; Foam structures; Lattice Boltzmann method; Non-Newtonian fluids

Foam dynamics in non-Newtonian fluids using Lattice Boltzmann Method and its application in food industry - Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Hussein, Mohamed; Delgado, Antonio (ProcessNet 2019, 2019)

Food foams simulations by the means of multicomponent lattice Boltzmann Method - Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Osorio Nesme, Anuhar; Hussein, Mohamed; Delgado, Antonio (9th European Postgraduate Fluid Dynamics Conference, 2019)

Heat transfer in deformable foams by the means of multicomponent Lattice Boltzmann Method - Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Hussein, Mohamed; Osorio Nesme, Anuhar; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
Foam propagation is a complex and challenging topic in food and chemical industry. Foam exists in several industrial applications such as food supply and discharge pipes, dairy products tanks and rectification columns. Foams often influence the mass, momentum and energy transport as well as the biochemical reactions. Consequently, this leads to a significant additional consumption of time and energy, and also to a loss of product quality and safety. The proposed approach is to apply a multi-component Lattice Boltzmann method, namely Shan-Chen pseudopotential model coupled with thermal LBM in order to simulate the complex heat transfer process in foams, taking into account the foam dynamics and deformation. The approach is to use multi-distribution functions for the multicomponent flow and temperature fields considering the different physical parameters for each phenomenon. The Lattice Boltzmann Method (LBM) has recently gained great attention in thermal flow field modelling, especially in complex media. One great advantage of the method is that it handles complex geometries and obstacles in a simple manner. LBM also gained much attention and success in the field of multicomponent and multiphase flows, one benefit is that it does not need an explicit additional algorithm for interface tracking. These simulations will provide a deeper insight in the foam dynamics and heat transfer process inside this nonhomogeneous medium. This can provide the basis for a prediction tool that regards the foaming causes and effects in several industrial processes. Several Industrial sectors with various products like beverages and milk can benefit from this tool, as the foaming in beverages’ filling and dairy production can be controlled and optimized on this basis. Other applications are chemical production facilities that deal with columns and evaporators which also encounter critical foaming issue
Keywords: Lattice Boltzmann Method; Multiphase-Multicomponent flow; Shan-Chen Pseudopotential Model; Thermal Flows; Food Foams

Helical Packing Columns for Preventing Foam Formation: Experimental and Numerical Investigations - Osorio Nesme, Anuhar; Hohagen, Hans; Topic, Nikola; Thünnesen, Julian; Mobarak, Mohammad Mobarak; Lyu, Wenjing; Jahn, Alexander; Kim, Sedong; Delgado, Antonio (Chemical Engineering & Technology, 2022)
Unwanted foaming and liquid bridging inside structured packings have a negative effect on the pressure drop during thermal separation processes. A novel helical design of a packing column for preventing foaming is presented. The effective interfacial area is calculated by numerical simulations. Different designs are analyzed by varying geometrical parameters such as helix pitch, channel opening angle, and number of channels. Different F-factor values and liquid loads are evaluated. Packings with larger helix pitch exhibited lower pressure drop and reduced effective interfacial area. Smaller channel opening angles increased the pressure drop and promoted unstable flow conditions. The novel packings show lower effective interfacial area than existing structured packings, but no foaming was observed in a wide range of operating conditions.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Foaming; Mass transfer; Packing columns; Pressure drop; Structured packing

Investigations on the possibility of Lattice Boltzmann as a Methodology for Flow Analysis in Subsonic Axial Compressor - Mobarak, Mohammad Mobarak; Hussein, Mohamed; Delgado, Antonio (Proceedings der 26. Fachtagung Experimentelle Strömungsmechanik, 2018)
Lattice Boltzmann Method (LBM) has recently gained great attention in the flow field modelling, especially in complex medium. One great advantage is the method of handling complex geometries and obstacles in a straight forward particle collision method. The proposed work is to apply a developed and validated Lattice Boltzmann model for incompressible turbulent fluid flows to a subsonic axial compressor with Reynold's number 300,000. The scheme's stability and its performance at higher Reynold's number were investigated for its validity especially at critical flow regimes in regard to the combined LBM Smagorinsky Large Eddy Simulation (LBMLES) Turbulence model. The developed LBM model is applied to investigate the flow inside a subsonic axial compressor, innovatively, this is the first time to be achieved in literature using LBM. Worth to mention, the benefit from LBM's particle-obstacle collision treatment was gained to catch the interaction of fluid with moving rotor and fixed stator blades. Achieved without the need of dynamic grid or moving frames with interfaces as in conventional computational methods in turbomachinery. Finally, the flow field was visualized, investigated and the available turbomachinery parameters were studied for different operating conditions. The error with the available experimental data from the study case is also discussed fairl
Keywords: Lattice Boltzmann Method; Turbulence Model; Turbomachinery; Subsonic Axial Compressor

Modelling and simulation of food foams with different material consistencies - Mobarak, Mohammad Mobarak; Gladbach, Katharina; Chen, Nan; Gatternig, Bernhard; Osorio Nesme, Anuhar; Hussein, Mohamed; Delgado, Antonio (GDL – Symposium Lebensmittelschäume, 2019)

On the Simulations of Thermal Liquid Foams Using Lattice Boltzmann Method - Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Delgado, Antonio (Energies, 2023)
Liquid foams exist in a wide variety of chemical and industrial processes, and they can contaminate the end-product and cause time and economical losses. Understanding and simulating foam is not a straightforward task, due to the highly dispersed time and length scales where the physical phenomena occur. Surfactants’ or proteins’ length scales are far beyond the capability of macroscopic and even mesoscopic numerical fluid solvers, yet the macroscales are still required to be resolved. Meanwhile, the lattice Boltzmann method (LBM) has gained much attention and success as a mesoscopic approach which can deal with complex multiphase multicomponent systems. The aim of this study is to implement LBM to simulate liquid foams while considering the accompanying thermal effects. A coupled multiphase multicomponent thermal flow model and its selected add-ons from the literature are tuned and explained, limitations and future suggestions are fairly discussed. Validations and a final study case are shown as an example for the proposed model and its applicability in thermal liquid foams. Finally, a delicate treatment to back couple the effect of temperature on the surface tension is proposed, hence considering one aspect of the Marangoni effect. Initial results show promising behavior, which can be material for future investigations.
Created from Fastlane, Scopus look-up
Keywords: heat transfer; lattice Boltzmann method; liquid foam; multiphase multicomponent flows

Untersuchungen zum Einsatz von Gashydraten als innovatives Triebmittel für Backwaren (AiF 21084 N) - Projektkurzbericht - Zettel, Viktoria; Mobarak, Mohammad Mobarak; Delgado, Antonio; Hitzmann, Bernd (2023)

Virtual and experimental studies for establishing an emerging bakery technology with substitution of baking yeast by particulate CO2 hydrates - Mobarak, Mohammad Mobarak; Claßen, Timo; Frühling, Yvonne; Srivastava, Shubhangi; Kollemparembil, Ann Mary; Grill, Bernhard; Zettel, Viktoria; Hitzmann, Bernd; Delgado, Antonio (HPBB2022, 2022)